PENINGKATAN KOMPETENSI PROFESIONALITAS GURU DALAM PROSES PEMBELAJARAN DI RA AT-THOHARIYYAH SUKASENANG SINDANGKASIH KABUPATEN CIAMIS - Tetin Nurfitri; Rosmini Rosmini; Munawar Hadiatin (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2021)
This study aims to find out the professional competence of teacher Raudhatul Athfal in the early childhood learning process at RA Ath-Thohariyyah in Nagrog Hamlet, Sukasuka Village, Sindangkasih District, Ciamis Regency. The method of this study is qualitative with data collection techniques use the method of observation, interviews and documentation. Checking the validity of the data is done by using triangulation techniques, namely comparing and checking the degree of trustworthiness of information obtained through different times and tools in qualitative methods. The results of the study found that the teacher had mastered the material, structure, and scientific mindset of the subjects being taught. It is done by observing students in mastering important aspects of a lesson and increasing students' interest and attention to the lesson. Mastery of competency standards and basic competencies in the field of development that are taught, every teacher is good enough to evaluate after the learning process is complete. Teachers have used information and communication technology to communicate and develop themselves, as well as apply learning media, but teaching teachers have not used technology media (LCD Projectors) by showing videos or films to help the teaching process. All professional competencies have been able to run optimally although there is still a need for improvement in all indicators.